Distress Levels among Parents of Active Duty Soldiers during Wartime - Bitton, Shahar; Tuval-Mashiach, Rivka; Freedman, Sara (Frontiers in Psychology, 2017)
OBJECTIVE: Military service is a highly stressful period both for the soldiers serving and for their parents. Surprisingly, parents’ experience has been mostly ignored in the research. This study’s goal is to shed light on the experience and distress levels of parents of active duty combat soldiers during Operation Protective Edge, a military operation carried out by the Israel Defense Forces (IDF) during July and August of 2014. METHOD: During the advanced stages of the operation, 69 parents of Israeli male combat soldiers (55 mothers and 14 fathers) completed an online survey measuring symptoms of Posttraumatic Stress Disorder (PTSD-Checklist-5) and distress (Brief Symptom Inventory–18). Participants were recruited using a convenience sample, by posting ads on the public Facebook pages of the researchers and of the groups dedicated to parents of Israeli soldiers. RESULTS: Parents' depression and anxiety symptom levels were higher than depression and anxiety symptom levels of the adult community norms in Israel. General distress rates of parents were similar to those presented by adults in southern Israel who were exposed for seven years to the ongoing threat of daily rocket fire from Gaza, and higher than rates of a non-threatened Israeli population. Finally, 20.2% of the parents presented PTSD-like symptoms, a higher percentage than the probable PTSD diagnosis rates that were found in the general population in Israel during previous terror waves. CONCLUSIONS: This study provides preliminary evidence of soldiers' parents' distress and indicates the need for a better understanding of the impact of military service on soldiers’ parents.